Urgensi Pendidikan Islam Berbasis Tauhid Perspektif Tafsir Ath-Thabari Analisis Pedagogi dalam Q.S At-Taubah ayat 31-33 - Choirun Nisa, Arifah; Burhanuddin, Enjang; Niswatul Malihah; Almujahid (Program Studi Ilmu Al-Qur'an dan Tafsir, 2025)
Islamic education is part of the teachings of Islam as a whole, because its goal is to create human beings who are always devoted to Allah and can achieve happiness in this world and the hereafter, as well as develop all aspects of life, including spiritual, intellectual, imaginative, physical, scientific, and linguistic. The concept of monotheism is the main foundation in Islamic education because monotheism is the foundation for all aspects of Muslim life. Tawhid means making Allah SWT the only true worship. According to him, Tauhid is also the basis of education that is to be given to future generations.This research method uses literature review which involves the identification, evaluation, and synthesis of various literature sources relevant to the research topic with a qualitative approach. This article contains a review of the concept of Islamic education in the meaning of monotheism contained in surah at taubah verses 31-33 where the result of the analysis is that with the existence of education we can distinguish between good and bad things, haram and halal things and can follow Allah's command to amar ma'ruf nahi munkar and convince his people that Allah SWT is the One God by sending His Messenger (Prophet Muhammad SAW) to be Guidance/role models for his people to the right path